2019
DOI: 10.1037/bul0000188
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for child sexual abuse victimization: A meta-analytic review.

Abstract: Experiencing child sexual abuse (CSA) is a major public health problem with serious consequences for CSA victims. For effective assessment and (preventive) intervention, knowledge on risk factors and their effects is crucial. Here, the aim was to synthesize research on associations between (putative) risk factors and CSA victimization. In total, 765 (putative) risk factors were extracted from 72 studies, which were classified into 35 risk domains. A series of three-level meta-analyses produced a significant me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
123
3
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(147 citation statements)
references
References 173 publications
8
123
3
13
Order By: Relevance
“…Parent training programs targeting the personal and problem-solving skills of parents showed significant smaller effects on child maltreatment compared with programs not targeting these skills. Several review studies showed that personal problems of parents, such as stress, anger and health problems, are important risk factors for child maltreatment [15,16,17]. Therefore, it could have been expected that addressing these problems in parent training programs contributes to the prevention or reduction of child maltreatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Parent training programs targeting the personal and problem-solving skills of parents showed significant smaller effects on child maltreatment compared with programs not targeting these skills. Several review studies showed that personal problems of parents, such as stress, anger and health problems, are important risk factors for child maltreatment [15,16,17]. Therefore, it could have been expected that addressing these problems in parent training programs contributes to the prevention or reduction of child maltreatment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, targeting the child’s anti-social behavior in parent training programs might not necessarily increase their effectiveness. Furthermore, when too much time and effort is spent on the child’s anti-social behavior, rather than on spending time and effort on parenting related issues, the program effectiveness may actually decrease, as these issues are more predictive of child maltreatment than factors related to the characteristics of the child [15,16,17]. This could explain the negative moderating effect of this program component.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the above, some of the core principles of the risk-need-responsivity model [63] could be applied to the prevention of child victimization [64]. Knowledge of the risk factors is vital for preventing or reducing violence, and for identifying the most suitable forms of support and intervention in order to address these risks in a proportionate manner.…”
Section: Increased Risk Of Violence Through the Lens Of Socioecologicmentioning
confidence: 99%
“…In his preconditional classic model, Finkelhor (1984) included factors of both perpetrator and victims’ individual characteristics and social features, incorporating unprotective surroundings and lack of non-offending parents’ presence/supervision, as well as social isolation as variables affecting the risk of CSA. In a recent metanalysis on risk factors and CSA victimization based on 72 studies, some of the strongest risks were attributed to parental problems and prior or concurrent forms of child abuse in the child’s home environment ( Assink et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%